Fish and salt: The successful recipe of White Nile Mesolithic hunter-gatherer-fishers. (April 2018) - Maritan, Lara; Iacumin, Paola; Zerboni, Andrea; Venturelli, Giampiero; Dal Sasso, Gregorio; Linseele, Veerle; Talamo, Sahra; Salvatori, Sandro; Usai, Donatella
Abstract: In prehistoric hunter-gatherer-fisher communities, demographic growth and a more sedentary life-style are usually associated with locally concentrated food resources. Technologies believed to have been employed for preserving excess food resources include, among many others, salting, smoking, and/or sun-drying of fish and meat. However, direct proof of salting is often lacking, as salt is highly soluble. We present here the first robust evidence of the earliest known examples of fish salting from Middle Mesolithic structures at an archaeological site in Central Sudan (7th millennium BC). A multidisciplinary approach was applied, including a contextual geoarchaeological study (field analysis; micromorphological and scanning electron microscopy), a mineralogical-microstructural analysis of salt crystallization (X-ray diffraction, scanning electron microscopy), and a chemical analysis of salt concentration (ionic chromatography) in the soil in which salted fish bones have been found. The results indicate that salting fish with the aim of preserving it was common at the site of Al Khiday since the Middle Mesolithic and this habit cannot be related to post-depositional precipitation due to aridification of the area. A clear-cut emphasis on fishing characterized the economy of the human population of the time. This foraging system, together with salting and storing fish seems to be closely connected with its nearly sedentary status. Graphical abstract: Highlights: The earliest use of salt for fish conservation is here proved in the Nile valley. Mineralogical and chemical analysis indicate the use of halite. This food conservation practice favoured sedentism in hunter-gatherer-fisher society.